2010
DOI: 10.1124/jpet.109.163691
|View full text |Cite
|
Sign up to set email alerts
|

Oral Treatment with a γ-Secretase Inhibitor Improves Long-Term Potentiation in a Mouse Model of Alzheimer's Disease

Abstract: The ␤-amyloid peptide (A␤) is thought to play a critical role in the pathophysiology of Alzheimer's disease (AD). To study the effects of A␤ on the brain, transgenic mouse models have been developed that express high levels of A␤. These mice show some features of AD, including amyloid plaques and mild cognitive impairment, but not others such as progressive neurodegeneration. We investigated the age-dependent effects of A␤ on synaptic physiology in Tg2576 mice that express human A␤. We report that both basal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 40 publications
5
34
1
Order By: Relevance
“…Object recognition is impaired in animal models of Alzheimer's disease (AD) (Taglialatela et al, 2009) and ID, such as Down syndrome (Belichenko et al, 2009;Fernandez et al, 2007) and Fragile X syndrome (Ventura et al, 2004). In these models, reduced LTP has been reported (Fernandez et al, 2007;Lauterborn et al, 2007;Townsend et al, 2010) along with derangement of Rho signaling (MendozaNaranjo et al, 2007;Petratos et al, 2008) and/or alterations of the dendritic tree/spines (Benavides-Piccione et al, 2004;Comery et al, 1997;Perez-Cruz et al, 2011). Experimental approaches based on Rho modulation have shown pre-clinical efficacy in animal models of ID (Bongmba et al, 2011;De Filippis et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Object recognition is impaired in animal models of Alzheimer's disease (AD) (Taglialatela et al, 2009) and ID, such as Down syndrome (Belichenko et al, 2009;Fernandez et al, 2007) and Fragile X syndrome (Ventura et al, 2004). In these models, reduced LTP has been reported (Fernandez et al, 2007;Lauterborn et al, 2007;Townsend et al, 2010) along with derangement of Rho signaling (MendozaNaranjo et al, 2007;Petratos et al, 2008) and/or alterations of the dendritic tree/spines (Benavides-Piccione et al, 2004;Comery et al, 1997;Perez-Cruz et al, 2011). Experimental approaches based on Rho modulation have shown pre-clinical efficacy in animal models of ID (Bongmba et al, 2011;De Filippis et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have demonstrated that synaptic plasticity is correlated with learning and memory (Kandel, 2001;VanGuilder et al, 2011). Therefore, we examined whether improved cognitive performance following BTA-EG 4 treatment is associated with altered synaptic function and plasticity.…”
Section: Bta-eg 4 Improves Cognitive Performance In the Absence Of Enmentioning
confidence: 99%
“…This presents an interesting point by implying that creating new synapses may benefit cognitive function not by enhancing LTP at individual synapses, but by allowing more synaptic contact points to form along the dendrite for potential information storage. It is of interest to note that some of the APP transgenic AD mouse models display larger LTP in younger age (Marchetti and Marie, 2011;Wang et al, 2012). It would be of interest to know whether BTA-EG 4 treatment in these young AD mouse models would show beneficial effects.…”
Section: Bta-eg 4 Alters Synapse Formation Through Ras Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…100 When another mouse model, Tg2576 mice, which also expressed mutant human APP and had an increased amyloid β burden, were fed a γ-secretase inhibitor to reduce amyloid β levels, there was a profound restoration of impaired long-term potentiation, confirming that amyloid β does affect synaptic plasticity. 101 To understand the mechanisms whereby amyloid β can influence synaptic plasticity, many groups have examined the effects of amyloid β peptide derived from different sources in organotypic hippocampal slice preparations. These studies have shown that naturally occurring amyloid β peptides obtained from spinal fluid 102 or directly from brains of individ uals with Alzheimer disease 103 and naturally secreted amyloid β oligos from cultured cells can affect long-term potentiation and synaptic density.…”
Section: Glutamatergic Receptors and App Processingmentioning
confidence: 99%